PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA PEMBELAJARAN SBDP KELAS IV DI SD 1 DASAN GERES - Rahmatillah, Siti Alfiyana; Sutiah, Sutiah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Elementary school learning requires learning media to be able to convey the learning objectives desired by the teacher, including SBDP learning. SBDP learning is often accompanied by monotony and participants are not interested in learning it because it is considered difficult. So you can use Google Sites for the learning process, Google Sites media is media that is easy to use for all groups, and Google Media is a container in the learning process in the 4.0 era for students. The purpose of learning is to see the effectiveness of using google sites media in elementary schools, and whether google sites media can attract students' learning interest. This research uses R&D research or the ADDIE model. The results of the research average percentage of 72% and 75% are in the good category. The media that was validated was then tested on Gueu and students obtained an average percentage of 85%, while in the small group trials, it was 88%, and in the large group it was 81.2%. Including practical media and can attract students' learning interest.